Integration of Augmented Reality Technology in Problem-Based Learning Models on Students' Critical Thinking Skills - Eva Julyanti; Nurlina Ariani Hrp; Laili Habibah Pasaribu (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study aims to analyze the influence of the integration of Augmented Reality (AR) technology in the Problem Based Learning model on students' critical thinking skills in integer material. This study uses a quantitative approach with a quasi-experimental method through a non-equivalent control group pretest-posttest design. The research population was all 60 students of class VII of MTs Amalianur. The research sample consisted of class VII-A with 30 students as the experimental class and class VII-B with 30 students as the control class. The data collection technique was carried out through a critical thinking ability test using descriptive essay questions given at the pretest and posttest stages. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using independent sample t-tests. The results of the study showed that the average posttest score of students increased compared to the pretest score, namely from 18.23 to 76.42. The results of the hypothesis testing show that the integration of Augmented Reality technology in the Problem Based Learning model has a positive influence on students' critical thinking skills. Thus, the use of Augmented Reality technology can be an effective learning innovation in supporting the development of students' critical thinking skills in mathematics learning.